Uji Efektivitas Beberapa Jenis Dekomposer dalam Pembuatan Bokashi dari Purun Tikus - Rahmi, Nadia; Rizali, Akhmad; Khamidah, Noor (Agroekotek View, 2024)
Purun rats are aquatic plants that grow fast and are able to adapt so that they become a problem in swamp waters due to population explosion. One form of utilization of this plant is to process it into bokashi which is useful  for adding nutrients in the soil as organic fertilizer. Bokashi is a fermented organic fertilizer. The process of making bokashi requires a decomposer, one of which is commonly used is EM-4. Along with the times and technology, many other types of commercial decomposers contain various microorganism that can break down organic matter, including M21 Decomposer and Biodex. This study aims to determine which types of decomposer is most effective in making bokashi from rat purun and whether the results of the decomposition of several types of decomposers in making bokashi from rat purun can meet SNI. This research was carried out in August 2021-October 2021 at the Seedling House of the Department of Agroecotechnology, Faculty of Agriculture, Lambung Mangkurat University. The results of this study ware analyzed descriptively by comparing with SNI 19-7030-2004. The treatment used in this study was D1=M21 Decomposer 13,95 g, D2=EM-4 28,92 g, and D3=Biodex 50 g. The results showed that the most effective treatment in making bokashi from purun mice was D3=Biodex 50 g, which could be seen from  the decrease in the C/N rasio to 10,26%, whicht was lower than treaments D1 and D2. Based on the results of the comparison with SNI 19-7030-2004 bokashi treatment D1, D2, and D3 with parameters of temperature, color, texture, odor, moisture content and chemical content in the form of N-total, C-Organic, P-total, rasio C/N, K-total, Ca-total, Mg-total, and Fe-total can meet SNI except for pH parameters.